2019
DOI: 10.1186/s40497-018-0120-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management: a roadmap for innovation in SMEs’ sector of Azad Jammu & Kashmir

Abstract: In this empirical study, we have examined the impact of knowledge management on organizational innovation capacity. Ultimate objective of existing research was to explore the role of knowledge management in encouraging innovation capacity in SMEs. Furthermore, this study also described role of knowledge management process to enhance knowledge repositories of SMEs. In order to understand knowledge management-innovation relationship, we collected data from SMEs across Azad Jammu and Kashmir. It was found that kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
0
12
0
1
Order By: Relevance
“…For instance, study of Mohammad and Roozbeh (2014), covering multiple sectors in North America reported significant knowledge management's impact on performance. Furthermore, it has been argued that knowledge management supports innovation (Cavusgil, Calantone, & Zhao, 2003;Hussain, Qurashi, Mujtaba, Waseem, & Iqbal, 2019). In context of innovation diffusion theory, when innovation is adopted by individuals, it indicates foundation as well as diffusion of innovation (Rogers, 2003).…”
Section: 1) Knowledge Management Innovation and Organizational Performancementioning
confidence: 99%
“…For instance, study of Mohammad and Roozbeh (2014), covering multiple sectors in North America reported significant knowledge management's impact on performance. Furthermore, it has been argued that knowledge management supports innovation (Cavusgil, Calantone, & Zhao, 2003;Hussain, Qurashi, Mujtaba, Waseem, & Iqbal, 2019). In context of innovation diffusion theory, when innovation is adopted by individuals, it indicates foundation as well as diffusion of innovation (Rogers, 2003).…”
Section: 1) Knowledge Management Innovation and Organizational Performancementioning
confidence: 99%
“…Knowledge management also helps in achieving organizational goals by integration of resources, encouraging employees and allowing organizations for gaining advantage through effective teamwork and synergy in addition to sharing of knowledge and expertise (Mishra & Bhaskar, 2011). Over and above ensuring informed decision making, it facilitates in sharing expertise and ultimately promotes collective perspectives ( López-Nicolás & Meroño-Cerdán, 2011;Hussain et al, 2019).…”
Section: Literature Review 21 Knowledge Managementmentioning
confidence: 99%
“…Pemasalahan yang dihadapi oleh pelaku UMKM adalah terbatasnya media yang digunakan untuk mempromosikan terkait UMKM [Prasmadewa and Tanone, 2016]. Dengan pengelolaan dan penerapan knowledge, akan dapat digunakan untuk mendukung UMKM dalam mewujudkan inovasi pendukung daya saing [Hussain et al, 2019].…”
Section: Usaha Kecil Mikro Menengah (Umkm)unclassified